(untitled) (Research, Society and Development, 2021)
According to the National Health Agency, obstetric violence affects 1 in 4 Brazilian women. Considering the number of practices of violence in prenatal, childbirth, and the puerperium, this article aimed to investigate the obstetric violence experienced and reported by women in the documentary “The Rebirth of Childbirth I” (free translation), produced in 2013, directed by Eduardo Chauvet, filmmaker, and Érica de Paula, psychologist. Considered as a milestone in the fight against obstetric violence in Brazil, this documentary brings testimonials from women in relation to their experiences during pregnancy, in this way, as a methodology, film analysis has been carried out, the discourse analysis has been used as a method, carried out from categories of analysis chosen from the narratives of these women, such as lack of information and induction of cesarean section, psychological violence such as obstetric violence, invasive procedures, and losses in the mother-baby relationship. As a result, it was shown that the reality of violence, caused by the lack of information and market conduct of health practices, contradicts the culture that romanticizes motherhood, pregnancy, and childbirth; offering an environment, services, and policies that place women in a situation of helplessness and violence, thus affecting their mental health. In outline, the way birth is approached is related to a social project and, therefore, there is a need to reformulate policies for prenatal and childbirth care, with the role of women being important, psychoeducational interventions for parents, being necessary to link gender and feminist studies to health and practice studies.